Private-sector led extension in Kenya’s dairy sector - Odhong’, Charles; Wilkes, Andreas; Dijk, Suzanne van (2018)
Kenya’s dairy processors have begun to invest in providing extension services to small holder dairy farmers in their own supply chains. Investment has positive returns for both processors and farmers. Each processor is developing their own model of extension service delivery and financing that complements and supports the activities of local governments, farmer cooperatives and other input providers in different ways. The public sector can support private sector led extension by ensuring the provision of public goods (e.g. vaccinations, road infrastructure) and key input supplies (e.g. credit), and by supporting stakeholders to learn how to address critical social and environmental concerns, and by capturing lessons from pilot innovations to support scaling up.